2016
DOI: 10.1371/journal.pone.0150060
|View full text |Cite
|
Sign up to set email alerts
|

BjuB.CYP79F1 Regulates Synthesis of Propyl Fraction of Aliphatic Glucosinolates in Oilseed Mustard Brassica juncea: Functional Validation through Genetic and Transgenic Approaches

Abstract: Among the different types of methionine-derived aliphatic glucosinolates (GS), sinigrin (2-propenyl), the final product in 3C GS biosynthetic pathway is considered very important as it has many pharmacological and therapeutic properties. In Brassica species, the candidate gene regulating synthesis of 3C GS remains ambiguous. Earlier reports of GSL-PRO, an ortholog of Arabidopsis thaliana gene At1g18500 as a probable candidate gene responsible for 3C GS biosynthesis in B. napus and B. oleracea could not be vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
(74 reference statements)
2
15
0
Order By: Relevance
“…This is consistent with the finding that among all biosynthetic enzymes, CYP79F2 exerts the strongest effect on pathway flux, with an outsized effect on propyl GSLs (i.e., GSLs with 3C side-chain lengths) [12]. Functional polymorphism at a CYP79F gene also underlies a QTL affecting the propyl fraction of GSLs in Brassica juncea [51], and separately underlies adaptive variation in the proportion of GSLs derived from branched-chain amino acids relative to methionine in Boechera stricta [52]. The association at CYP79F paralogs was recovered in our re-analysis of one European Arabidopsis dataset (Fig.…”
Section: (C) Gwas Within the Local Tou-a Population Reveals Known And Novel Variants Shaping Aliphatic Glucosinolate Profilessupporting
confidence: 89%
“…This is consistent with the finding that among all biosynthetic enzymes, CYP79F2 exerts the strongest effect on pathway flux, with an outsized effect on propyl GSLs (i.e., GSLs with 3C side-chain lengths) [12]. Functional polymorphism at a CYP79F gene also underlies a QTL affecting the propyl fraction of GSLs in Brassica juncea [51], and separately underlies adaptive variation in the proportion of GSLs derived from branched-chain amino acids relative to methionine in Boechera stricta [52]. The association at CYP79F paralogs was recovered in our re-analysis of one European Arabidopsis dataset (Fig.…”
Section: (C) Gwas Within the Local Tou-a Population Reveals Known And Novel Variants Shaping Aliphatic Glucosinolate Profilessupporting
confidence: 89%
“…In Arabidopsis , MeJA was reported to induce some CYP genes that enhanced the indolic glucosinolate production by 3- to 4-fold [24]. However, in some recent studies the BjuCYP83A1 and CYP79F1 genes were found to regulate aliphatic glucosinolate biosynthesis in B. juncea [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in the GSL biosynthesis pathways have been identified in many plant species. However, only a few genes, such as cytochrome P450 83A1 (CYP83A1) (Meenu et al 2015), dihomomethionine N-hydroxylase (CYP79F1) (Sharma et al 2016), and transcription factor MYB28 (Augustine et al 2013), have been reported in mustard.…”
Section: Introductionmentioning
confidence: 99%